Rubber Duck Toy as a Happy Metaphor in the Creation of Painting Artworks - Qurani, Cllauvitra Rheyna; Susanto, Moh. Rusnoto; Cahyono, Nugroho Heri (V-art: Journal of Fine Art, 2025)
This art research explores rubber duck toys as a metaphor for happiness, representing childhood memories and positive emotions evoked by simple things. The objectives of this art creation are: (1) to elaborate the concept of happiness through the symbolism of rubber duck toys, (2) to develop creative ideas as artistic expressions in painting, and (3) to explore techniques and concepts that enhance the visualization of artworks. The urgency of this project lies in uncovering the potential of everyday objects to convey philosophical and aesthetic meanings that can be universally appreciated. The method employed is exploration, which includes gathering references, developing ideas, and creating artworks using oil paint on canvas. The exploratory process involved observing the shape, color, and characteristics of rubber duck toys and transforming them metaphorically within the context of happiness. This creation resulted in seven paintings of various sizes, emphasizing aesthetics, narratives, and emotions.The outcomes of this project, represented by paintings, introduce the aesthetics of rubber duck toys, provide insights into painting based on everyday objects, and inspire appreciation for the simplicity of often-overlooked happiness. Beyond being a medium of expression, these artworks serve as a reflection of childhood memories for the audience.